Bilingual Learners and Social Equity Critical Approaches to Systemic Functional Linguistics (Educational Linguistics,, 2018)
This volume explores how educators conceptualized and implemented critical approaches to systemic functional linguistics that support bilingual students in appropriating and challenging dominant knowledge domains in K-16 contexts. The researchers exhibit a shared commitment to enacting a culturally sustaining SFL praxis that validates multilingual meaning making, pushes against social inequity, and fosters creative re-mixing of available semiotic resources. It should prove a valuable resource for students, teachers and researchers interested in applied linguistics, education and critical theory.